A Cyclotide Isolated from Noisettia orchidiflora (Violaceae) - Bobey, Antonio Fernández [UNESP]; Pinto, Meri Emili Ferreira [UNESP]; Cilli, Eduardo Maffud [UNESP]; Lopes, Norberto Peporine; Bolzani, Vanderlan Da Silva [UNESP] (Thieme, 2018)
Biologically active cyclotides have been found on some flowering plants species and are involved in the role of the plant protection. As part of studies focusing on peptides from Brazilian plant species, we are reporting the detection by LC-MS of several cyclotides from leaves and stems of Noisettia orchidiflora (Violaceae). From stems it was possible to isolate and characterize a cyclotide named Nor A. Its primary structure (amino acid sequence) was established by MALDI-TOF-MS, based on the y- and b- type ion series, after reduction and alkylation reactions, as well as enzymatic digestion using the enzymes endoproteinase glutamic acid (endoGlu-C), trypsin, and chymotrypsin. Furthermore, the amino acid analysis was also described.
Keywords: cyclic peptide; cyclotide; MALDI TOF/TOF; Noisettia orchidiflora; Nor A; Violaceae